Biased-corrected richness estimates for the Amazonian tree flora - ter Steege, Hans; Prado, Paulo I.; Lima, Renato A. F. de; Pos, Edwin; de Souza Coelho, Luiz; de Andrade Lima Filho, Diogenes; Salomão, Rafael P.; Amaral, Iêda Leão; de Almeida Matos, Francisca Dionízia; Castilho, Carolina V.; Phillips, Oliver L.; Guevara, Juan Ernesto; et al. (Springer Nature, 2020)
Amazonian forests are extraordinarily diverse, but the estimated species richness is very much debated. Here, we apply an ensemble of parametric estimators and a novel technique that includes conspecific spatial aggregation to an extended database of forest plots with up-to-date taxonomy. We show that the species abundance distribution of Amazonia is best approximated by a logseries with aggregated individuals, where aggregation increases with rarity. By averaging several methods to estimate total richness, we confirm that over 15,000 tree species are expected to occur in Amazonia. We also show that using ten times the number of plots would result in an increase to just ~50% of those 15,000 estimated species. To get a more complete sample of all tree species, rigorous field campaigns may be needed but the number of trees in Amazonia will remain an estimate for years to come.